Tourism development in the borderlands of Romania: A case study of the Danube Gorge–Iron Gates - Băbăț, Andrei-Florin; Pavel, Sorin (Quaestiones Geographicae, 2022)
Border areas are a real challenge for tourism development. Usually associated with the periphery from a socio-economic point of view, these areas often have natural potential and attractive landscapes that have been little transformed by human activity and numerous historical and cultural tourist attractions. Although these areas have considerable tourism potential, this is not sufficient for the sustainable development of tourism and the exploitation of this potential is strongly influenced by the degree of permeability of the border. This is the case of the Romanian-Serbian border, which overlaps the most spectacular sector of the Danube – the Iron Gates Gorge. The main aim of this article is to analyse the role of tourism in the development of border areas and how it functions in a particular territorial context: the Danube Gorge located at the border between Romania and Serbia. The Romanian-Serbian border currently functions as an external border of the European Union in a favourable historical and political context, given the tradition of good neighbourliness between the two entities, the states located on either side of the Danube. However, the communist period altered the prospects for tourism development in this region through a very drastic and controlled border regime, even though the area benefited from major investment projects, such as the dam and hydroelectric power station at Porțile de Fier, built in the 1970s in cooperation with the former Yugoslavia. An analysis of the statistical data on tourism development shows that tourist traffic is on the increase, although there is a contradiction between the upward trend in tourist flows and the backwardness of large-scale tourist infrastructure, with the dominant type of accommodation being small, flexible, and rural accommodation that does not require large investments. The results presented in this article can be summarised in the general conclusion that the development of tourism in the Danube Gorge–Iron Gates remains dependent on the political factor and the border regime, even though the region has a remarkable tourism potential.